2007
DOI: 10.1200/jco.2006.08.8344
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II Study of Fertility-Sparing Treatment With Medroxyprogesterone Acetate for Endometrial Carcinoma and Atypical Hyperplasia in Young Women

Abstract: The efficacy of fertility-sparing treatment with a high-dose of MPA for EC and AH was proven by this prospective trial. Even in responders, however, close follow-up is required because of the substantial rate of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
279
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(297 citation statements)
references
References 18 publications
12
279
2
4
Order By: Relevance
“…Studies at various institutions have reported the results of fertility-sparing treatment for EC using progesterone preparations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, as the number of cases have been low, the efficacy of such treatment has yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Studies at various institutions have reported the results of fertility-sparing treatment for EC using progesterone preparations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, as the number of cases have been low, the efficacy of such treatment has yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Cases in which extrauterine metastasis occurred during conservative therapy, such as those reported by Imai et al and Ota et al, were also excluded because such cases can be treated by standard surgery. Thus, 13 cases of extrauterine recurrence after temporary remission are listed in Table 2 [3,[8][9][10][11][12][13][14]. Six of these cases had ovarian lesions as the extrauterine site.…”
Section: Discussionmentioning
confidence: 99%
“…This therapy is indicated for patients with grade 1 endometrioid histology and very early stage cancer. Good hormonal response rates between 57% and 75% have been achieved, but the relapse rates after remission are also high, varying between 47% in follow-up of 7 to 22 months and 89% after follow-up of over 30 months [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…To summarize the domestic and overseas reports on progestin therapy applied as fertility-preserving therapy in 1997 through 2008, the lesions disappeared in 164 (75%) of the 218 cases of endometrial cancer (corresponding to G1 endometrioid adenocarcinoma, FIGO 1988 surgical stage Ia) in response to progestin therapy. Among these 164 cases showing disappearance of lesions, recurrence was later noted in 53 (36%) of the 148 cases where information on the presence/absence of recurrence was available (Table I) (14,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). When progestin therapy was applied to 47 cases of atypical endometrial hyperplasia, 42 cases (89%) showed disappearance of lesions, and 8 (19%) of these 42 cases later showed recurrence (Table II) (26,27,31,35).…”
Section: Progestin Therapy For Endometrial Cancermentioning
confidence: 99%
“…Among these 164 cases showing disappearance of lesions, recurrence was later noted in 53 (36%) of the 148 cases where information on the presence/absence of recurrence was available (Table I) (14,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). When progestin therapy was applied to 47 cases of atypical endometrial hyperplasia, 42 cases (89%) showed disappearance of lesions, and 8 (19%) of these 42 cases later showed recurrence (Table II) (26,27,31,35). Regarding the efficacy of progestin therapy on endometrial cancer, Montz et al reported that when progestin therapy was administered to cases of G1 endometrial cancer (FIGO 1988 surgical stage Ia) not indicated for surgery for reasons of influence of complications or preservation of fertility, the tumor was histologically rated as negative in 7 of the 11 cases at 6 months and 6 of the 8 cases at 12 months after the start of treatment (36).…”
Section: Progestin Therapy For Endometrial Cancermentioning
confidence: 99%